Classical Temples and Industrial Stores: Survey Analysis of Historic Unreinforced Masonry (URM) Precincts to Inform Urban Seismic Risk Mitigation. Issue 7 (17th November 2018) - Vallis, Stacy; Gálvez, Francisco; Swidan, Moustafa; Orchiston, Caroline; Ingham, Jason
ABSTRACT: Oamaru, Winton, and Invercargill feature some of New Zealand's most intact heritage precincts that are confronted by ongoing threats of seismic activity. The 2010/2011 Canterbury earthquake sequence and Canterbury Earthquakes Royal Commission of 2012, identified a nationwide trend through the proportion of deaths that occurred in public places as a result of the prevalent historic unreinforced masonry (URM) building stock. The reported study was undertaken to address urban safety and seismic risk mitigation through the lens of heritage conservation. The range of classically designed public buildings and industrial warehouses in the South Island of New Zealand were often produced by singular architectural practices, using locally sourced materials and construction techniques. It is vital to incorporate an examination of unique architectural qualities within urban seismic risk assessment and mitigation. Historic urban layout, architectural deployment of masonry, and extent of retrofits were recorded through onsite visual surveys via Geographical Information Systems and three-dimensional representation technologies. Extending the scope of information collected for engineering seismic risk assessment by focusing on the historical architectural context informs the selection of future mitigation measures. Oamaru, Winton, and Invercargill present intriguing case studies for multidisciplinary analysis, prior to testing urban-scale survey approaches within comparable historic centers across New Zealand.